Ultraviolet Photometry and Habitable Zones of over 2700 Planet-hosting Stars - Xue Li; Song Wang; Henggeng Han; Jifeng Liu (The Astrophysical Journal Supplement Series)
The ongoing discovery of exoplanets has sparked significant interest in finding suitable worlds that could potentially support life. Stellar ultraviolet (UV; 100–3000 Å) radiation may play a crucial role in determining the habitability of their planets. In this paper, we conducted a detailed analysis of the UV photometry of over 2700 host stars with confirmed planets, using observational data from the Galaxy Evolution Explorer and Swift Ultraviolet/Optical Telescope missions. We performed aperture photometry on single-exposure images and provided photometric catalogs that can be used to explore a wide range of scientific questions, such as stellar UV activity and planet habitability. By calculating the circumstellar habitable zone and UV habitable zone, we found that fewer than 100 exoplanets fall within both of these zones, with the majority being gas giants. We also examined stellar activity based on their far-UV (FUV) and near-UV (NUV) emissions. We found the FUV−NUV color more effectively represents stellar activity compared to the ${R}_{FUV}^{{′} }$ and ${R}_{NUV}^{{′} }$ indices. The Sun’s low FUV emission and moderate NUV emission highlight its uniqueness among (solar-like) stars.